Analysis of Project Acceleration Implementation Using the CPM and PERT at Lettu Imam Building (Universitas 17 Agustus 1945 Surabaya, 2022)
The implementation of construction projects generally has a predetermined time limit. To achieve the time limit, planning and controlling are necessary. Planning can determine what work needs to be done and when it is done, what resources are needed, and what risks may arise. Clear activity targets can be identified for each activity. The case study in this research is Lettu Imam Building Construction Project in the OPD Office Complex of Pasuruan Regency. This study uses the Critical Path Method (CPM) to determine the work items passed through the critical path and the Project Evaluation and Review Technique (PERT) to determine the probability of project success. The results of the analysis using the Critical Path Method are 14 work items that were on the critical path A1 - A2 - A3 - B1 - C1 - C2 - C3 - C4 - C5 - C6 - C7 - C8 - C9 - D1. And the result analysis using Project Evaluation and Review Technique has a project completion probability of 89.43% - 99.37%, with the project implementation duration being 162 - 164 days. Keywords: Critical Path, Critical Path Method, Planning, Probability, Project Evaluation and Review Technique